2012
DOI: 10.1172/jci63474
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in 2 distinct genetic pathways result in cerebral cavernous malformations in mice

Abstract: The affiliation for Sang-Hwa Yang and Sang-Kyou Lee was incorrect. In addition, the sentence in Acknowledgments providing the source for Sang-Kyou Lee's research grant was omitted. The correct affiliations list appears above. The omitted sentence is below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 0 publications
1
37
0
Order By: Relevance
“…11,167 In addition, deletion of CCM3 interrupts lumen formation but not the development of branchial arch arteries. 168,169 At the biochemical level, CCM2 is required for maintaining the cytoskeleton and limiting RHOA activation.…”
Section: Ccm Proteins In Endothelial Polaritymentioning
confidence: 99%
See 1 more Smart Citation
“…11,167 In addition, deletion of CCM3 interrupts lumen formation but not the development of branchial arch arteries. 168,169 At the biochemical level, CCM2 is required for maintaining the cytoskeleton and limiting RHOA activation.…”
Section: Ccm Proteins In Endothelial Polaritymentioning
confidence: 99%
“…11 The effect of CCM3 on RHOA activation is the subject of controversy. 169,170 Instead, CCM3 is located on the Golgi apparatus and stabilizes the germinal center kinase III (GCKIII). 171 In support of a pathogenic role of GCKIII in CCMs, overexpression of the GCKIII kinase STK25b rescued the vascular defects in zebrafish deficient in CCM3.…”
Section: Ccm Proteins In Endothelial Polaritymentioning
confidence: 99%
“…25,26,32,33 Studies in mice have since definitively confirmed and significantly extended these findings. 25,[34][35][36][37][38][39][40] Bubblehead (bbh) and redhead (rhd) These mutants represent a class of zebrafish vascular mutants isolated from forward genetic screens for defects in vascular integrity. Mutants in this broader class displayed brain hemorrhaging with mild additional cardiovascular defects and several of these mutants remain to be characterized.…”
Section: Endothelial Cell-cell Adhesion In Developmentmentioning
confidence: 99%
“…Whereas neural-and SMC-specific depletion of Ccm2 has no effect, EC-specific loss of Ccm2 or Pdcd10 in mice results in formation of CCMs (Boulday et al 2009;Whitehead et al 2009;Chan et al 2011). The pathways involved in lesion formation are, however, different: Whereas loss of Krit1 or Ccm2 leads to RhoA activation, Pdcd10 binds GCKIII (germinal center kinase III) family kinases and plays a role in EC lumen formation (Chan et al 2011).…”
Section: Trp53mentioning
confidence: 98%